Plant Competition in Cropping Systems - Dunea, Daniel (IntechOpen, 2018)
In the coming years, farmers will face difficult challenges throughout the world in terms of climate change, water scarcity, and environmental issues caused by conventional agricultural technologies. Effective management of natural resources can be encouraged by orienting the common agricultural practices towards the functional biodiversity concept in designing and implementing sustainable and eco-friendly cropping systems. In the framework of polycrop science, this book provides basic principles and several case studies of polycrop utilization in various regions of the world as a method of functional biodiversity amplification through species associations that maximize the productivity per unit of land area, suppress the growth and development of weeds, and reduce the amount of harmful pests and insects.